Daidzein-rich isoflavone aglycones inhibit cell growth and inflammation in endometriosis. Issue 181 (July 2018) - Takaoka, O.; Mori, T.; Ito, F.; Okimura, H.; Kataoka, H.; Tanaka, Y.; Koshiba, A.; Kusuki, I.; Shigehiro, S.; Amami, T.; Kitawaki, J.
Highlights: We proposed the efficacy of DRIAs and dietary supplement on endometriosis. DRIAs inhibit cell proliferation in human endometriotic stromal cells. DRIAs reduce inflammatory cytokines and exhibit ERβ-mediated activity. DRIAs reduce the extent of endometriosis-like lesions in a mouse model. DRIAs might be a potential therapeutic option for management of endometriosis. Abstract: Endometriosis is an estrogen-dependent disease, and isoflavones interact with estrogen receptors. The purposes of this study are to investigate the in vitro and in vivo effects of daidzein-rich isoflavone aglycones (DRIAs), dietary supplements, on cellular proliferation in endometriosis. Stromal cells isolated from ovarian endometrioma (OESCs) and normal endometrium (NESCs) were cultured with DRIAs, i.e., each of the DRIA components (daidzein, genistein, or glycitein), or isoflavone glycosides (IG; DRIA precursors). A mouse model of endometriosis was established by transplanting donor-mouse uterine fragments into recipient mice. Our results showed that DRIAs (0.2–20 μM) inhibited the proliferation of OESCs ( P  < 0.05 for 0.2 μM; P  < 0.01 for 2 and 20 μM) but not of NESCs. However, daidzein, genistein, glycitein, and IG did not inhibit their proliferation. DRIA-induced suppression was reversed by inhibition of the estrogen receptor (ER)β by an antagonist, PHTPP, or by ERβ siRNA ( P  < 0.05), but not by MPP, an ERα antagonist. In OESCs, DRIAs led to reduced expression of IL-6, IL-8, COX-2, and aromatase, as well as reduced aromatase activity, serum glucocorticoid-regulated kinase levels, and PGE2 levels ( P  < 0.05). Western blot and immunofluorescence assays revealed that DRIAs inhibited TNF-α-induced IκB phosphorylation and p65 uptake into the nuclei of OESCs. In the mouse model, a DRIA-containing feed significantly decreased the number, weight, and Ki-67 proliferative activity of endometriosis-like lesions compared to in mice fed with an IG-containing feed and the control feed ( P  < 0.01). In conclusion, DRIAs inhibit cellular proliferation in endometriosis, thus representing a potential therapeutic option for the management of endometriosis.